Analisis Hubungan Kecepatan Pemberian Cairan dengan Perubahan Kondisi Hemodinamik pada Pasien Dengue - Nabila, Nazia; Safariyah, Erna; Hamzah, Amir; Abidinsah, Zainal (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the relationship between fluid administration speed and hemodynamic changes in dengue patients in the Emergency Department (ED). The method used was quantitative with a correlational design and a cross-sectional approach. The study subjects were 20 dengue patients selected through purposive sampling. Data analysis used the Chi-Square statistical test to examine the relationship between variables. The study demonstrated that